A review of cloud computing and its opportunities in the development of information systems for SMEs - Cunha, Carlos R. (2016)
This paper reviews the main characteristics of cloud computing, where they are exposed their main components and ways of use. In addition to the technological review that is done, is also carried out a critical analysis of their potential and challenges in the context of SMEs. To understand how cloud computing can lead to a powerful ally of SMEs in the context of organizational competitiveness in a world where the role of information systems for a long time proved decisive, it is a reflection that the SMEs, whose core business is not technology, need to carry out.